Integration of Trivia Game Within the Metaverse Mall for Public Services in the City of Semarang - Widianto, Daniel Prasetya; Sanjaya, Ridwan; Pamudji, Andre Kurniawan (Journal of Business and Technology, 2024)
The lack of education regarding the metaverse mall application for public services has left the public confused when engaging in public service activities within it. To address this issue, a trivia game titled "MPP Quiz" was created with the aim of understanding user responses to the implementation of an educational trivia game packaged with metaverse technology. The chosen research method is the waterfall model because its stages are well-suited for application in this study. The data collection method employed quantitative techniques by distributing questionnaires to respondents who had previously played the MPP Quiz game. After collecting the data, it was processed using the SPSS application to determine the level of validity, reliability, and correlation between the tested variables. Based on the conducted tests, it can be concluded that the MPP quiz game qualifies as an educational medium and introduction to the public service system in Semarang city, as the values of variables tested for validity, reliability, and correlation exceed the set standards.